Localization-assisted stimulated Brillouin scattering spectroscopy - Giulia Zanini; Giuliano Scarcelli (APL Photonics, 2022)
Brillouin spectroscopy has emerged as a promising modality to noninvasively probe the mechanical properties of biologically relevant materials. Stimulated Brillouin scattering (SBS) has the potential to improve measurement speed and resolution by exploiting a resonant amplification of the scattered signal, yet current SBS spectrometers have not provided significant improvements due to fundamental and practical limitations of illumination and detection parameters. To overcome this challenge, here we derive a signal localization theory for the Brillouin spectral domain and accordingly design an SBS spectrometer with much improved performances compared to state-of-the-art systems. We present experimental and simulated data validating our theory, which result in a tenfold improvement in acquisition speed, or an order of magnitude improved spectral precision, for SBS spectral measurements when properly optimizing the SBS photon detection architecture.